Osteoarthritis, cerebrovascular dysfunction and the common denominator of inflammation: a narrative review. Issue 4 (April 2018) - Al-Khazraji, B.K.; Appleton, C.T.; Beier, F.; Birmingham, T.B.; Shoemaker, J.K.
Summary: Objective: Population-based cohort studies suggest an association between osteoarthritis (OA) and cerebrovascular disease, yet the mechanisms underlying vascular comorbidities in OA remain unclear. The purpose of this narrative review is to discuss the literature examining inflammation in OA with a focus on physiological mechanisms, and whether overlapping mechanisms exist in cerebrovascular dysfunction. Method: A literature search was conducted in PubMed using combinations of search terms: osteoarthritis, cerebrovascular (disease/dysfunction/risk), cardiovascular (disease/dysfunction/risk), aging/ageing, inflammation, inflammatory mediators, cytokine, c-reactive protein, interleukin, advanced glycation end-products, metabolic syndrome, reactive oxidative species, cognitive impairment, (vascular-related) dementia, small cerebral vessel disease, endothelial function, blood–brain barrier, gender/sex, hypertension, peripheral vascular health, and physical activity . Reference lists of identified articles were also researched manually. Results: Overlapping inflammatory factors that may contribute to onset and progression of both OA and cerebrovascular dysfunction are presented. We describe oxidative mechanisms involving pro-inflammatory cytokines and oxidative species, advanced glycation end-products, sex hormones, microvascular dysfunction and osteoprotegerin, and their specific roles in potentially contributing to OA and cerebrovascular dysfunction. Conclusion: Synthesis of the current literature suggests future investigations may benefit from directly testing cerebrovascular hemodynamics and cognitive function in individuals with or at risk of OA to elucidate common physiological mechanisms.